Yak Domestication: A Review of Linguistic, Archaeological, and Genetic Evidence - Guillaume Jacques; Jade d'Alpoim Guedes; Shuya Zhang (Ethnobiology Letters, 2021)
Yak, a species of bovid uniquely adapted to high-altitude environments, plays a critical role in the life of the inhabitants of the Tibetan Plateau and neighboring areas. There is currently no consensus on when these animals may have been domesticated. In this paper, we review the archaeological, genetic, and linguistic evidence relevant to this question, and suggest that the domestication took place following hybridization with taurine cattle from the end of the fourth millennium BCE. This study also shows that the original domesticators of yaks included not only the ancestors of the Tibetans, but also Rgyalrongic speaking people from Eastern Tibet.